The Families Resilience Issue dealing with the Village Empowerment Program: Implication for Social Development - Hermansah, Tantan; Kusmana, Kusmana (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
The article explores concerning evaluation program that the government has implemented in people's villages. This study conducted a reformulation policy to increase better family resilience in the rural areas. The study uses a qualitative method and collecting data with interviews, documentation, and observation. The research finds that community development in the village showed a new social sustainability pattern with three main goals: structure, culture, and process. It is a new program considering establishing a reformulation of social policy as an objective program that promotes sustainable development. While the program's implementation faced an obstacle driven by the local elite, it gained collaborative action with the regency government. Thus, the village development's family resilience failed not to internalize to deeply life confidence, but they do not feel they have awareness. Also, they still consider that family resilience is not a part of community development program, so it is not implemented very well. In summary, the planning village development has been the case to the local elite who are still focal figures to be “a small kingship” in the village.